Working from home and mental health: Giving employees a choice does make a difference - Uwe Jirjahn; Cinzia Rienzo (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2025)
Previous studies on working from home (WFH) and employee well-being have produced extremely conflicting results. We hypothesize that giving workers a choice over whether to use WFH plays a crucial role in the consequences for well-being. This perspective has a series of testable implications for empirical work. Using panel data from the United Kingdom, our fixed effects estimates show that not only the actual use, but also the pure availability of WFH is associated with improved job-related and overall mental health. Not controlling for the pure availability of WFH implies that the positive influence of the actual use of WFH is underestimated in the regressions. However, we find a positive association between the use of WFH and overall mental health only for the years before and after the pandemic. The association was negative during the COVID-19 crisis where WFH was largely enforced. Finally, gender moderates the influence of WFH on mental health. For women, both the actual use and the pure availability of WFH are positively associated job-related and overall mental health. For men, we find a more mixed pattern where either only the pure availability or only the actual use has an influence on mental health. This indicates that men are more likely to over- or underrate the consequences of WFH than women.
Keywords: I10; I31; J16; J22; M50; 330; Remote Work; Freedom of Choice; Pandemic; Mental Well-Being; Gender